2022
DOI: 10.1155/2022/2663812
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Staphylococcus aureus α‐Hemolysin Production Using Nanocurcumin Capped Au@ZnO Nanocomposite

Abstract: Nanoparticles of gold with zinc oxide (Au@ZnO NPs) were prepared by laser ablation and then capped with curcumin nanoparticles (Cur-Au@ZnO NPs). The synthesized NPs were characterized using different techniques, including transmission electron microscopy (TEM), Fourier-transform infrared spectroscopy (FTIR), UV-visible spectroscopy, and X-ray diffraction. In addition, the ability of NPs as a promising antibacterial agent was tested against Staphylococcus aureus through the agar well diffusion method and AO/EtB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 78 publications
1
27
0
Order By: Relevance
“…The antibacterial susceptibility of Ocimum sanctum leaf and Bi-TiO 2 nanoparticles is assessed using the disc diffusion technique. The antibacterial capabilities of tulsi extract and Bi-TiO 2 nanoparticles were investigated using Gram-positive and Gram-negative bacteria as model microorganisms, such as E. coli and S. aureus [ 23 ]. To prepare the nutritional agar plate, all glassware is sterilized in a 120°C autoclave for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…The antibacterial susceptibility of Ocimum sanctum leaf and Bi-TiO 2 nanoparticles is assessed using the disc diffusion technique. The antibacterial capabilities of tulsi extract and Bi-TiO 2 nanoparticles were investigated using Gram-positive and Gram-negative bacteria as model microorganisms, such as E. coli and S. aureus [ 23 ]. To prepare the nutritional agar plate, all glassware is sterilized in a 120°C autoclave for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from their antibacterial, antioxidant, cytotoxic, hemolytic, and antiviral properties, ZnO NPs have many other biological and medicinal applications [ 123 ]. It has been reported that cancer was identified as the second most common cause of dysphoria in humans, after cardiovascular diseases [ 124 ].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…The chemical features of BC-CuONPs were recorded by FTIR (Bruker Tensor 27, Biotage, Germany; scanning range of 4000–400 cm −1 ; resolution of 4 cm −1 in the transmittance mode). The dried powder of biosynthesized CuONPs powder was mixed with potassium bromide and pressed into the disc for FTIR analysis 39 , 40 . The chemical composition of oxide CuONPs was analyzed by a X-ray photoelectron spectroscopy (XPS) analyzer (BESTEC, Germany) 41 , 42 .…”
Section: Methodsmentioning
confidence: 99%